Postinfectious syndrome of convalescentsixodes tick-borne borreliosis - O. N. Sumlivaya; N. N. Vorobyeva; Yu. V. Karakulova (Журнал инфектологии, 2014)
The aim: to study the psycho-vegetative status of the quantitative contents of serotonin in blood platelets in patients after the Ixodes tick-borne borreliosis, to evaluate the clinical efficiency treatment by adamantilfenilamin of postinfection asthenia.Materials and methods: there was clinical supervision and inspection conducted of 118 convalescents borreliosis after a course of inpatient treatment. All patients were examined using psychovegetative tests. Platelet serotonin concentration levels were measured by enzyme immunoassay. For the treatment of postinfectious asthenia 36 convalescents received adamantilbromfenilamin in a dose of 100 mg for 25 days.Results: when tested convalescents marked change in indicators of emotional and personality disorders. Quantitative study of blood platelet serotonin content revealed a significant decrease in this indicator relative to control values. Study the correlations between obtained when testing the psycho-emotional parameters and platelet serotonin levels showed a negative correlation between serotonin and an indicator of reactive anxiety (R = -0,81, p <0,05). To correct these violations convalescents with severe asthenia postinfection were treated adamantilfenilamin. Established clinical efficacy contributing to the improvement of the quality of life.Conclusion: the research of neurotransmitter serotonin in patients during the convalescence period after borreliosis possible to evaluate the extent of potential damage to the nervous tissue in the inflammatory process and its involvement in the formation of anxiety and depressive symptoms. adamantilbromfenilamin can be recommended for rehabilitation patients with residual effects in the form of postinfectious asthenia.